Crystal structure of the human mitochondrial chaperonin symmetrical football complex - Nisemblat, Shahar (Proc Natl Acad Sci U S A, 2015)
Human mitochondria harbor a single type I chaperonin system that is generally thought to function via a unique single-ring intermediate. To date, no crystal structure has been published for any mammalian type I chaperonin complex. In this study, we describe the crystal structure of a football-shaped, double-ring human mitochondrial chaperonin complex at 3.15 Å, which is a novel intermediate, likely representing the complex in an early stage of dissociation. Interestingly, the mitochondrial chaperonin was captured in a state that exhibits subunit asymmetry within the rings and nucleotide symmetry between the rings. Moreover, the chaperonin tetradecamers show a different interring subunit arrangement when compared to GroEL. Our findings suggest that the mitochondrial chaperonins use a mechanism that is distinct from the mechanism of the well-studied Escherichia coli system.